A palavra de Peron: análise do discurso e da política trabalhista argentina (1943-1949) - Cristina Isabel Abreu Campolina de Sa (2007)
This dissertation will discuss Juan Domingo Peróns labor policy in Argentina since his activities in the Labor and Prevision Secretary, starting in 1943, until the incorporation of the Workers Rights in the countrys Magna Letter in the 1949 Constitutional Reform. Through an effective labor policy associated with a corporative discourse and practice, Perón received the support of the Argentine working class until he was overthrown from power by the Liberator Revolution in 1955. This text will analyze Peróns speeches, the images used by him to validate his power, how the unions were adhering, little by little, to the official policy and the position assumed by the Communist and Socialist Parties.